1992
DOI: 10.1093/hmg/1.4.229
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutations of the APC gene in colorectal tumors: mutation cluster region in the APC gene

Abstract: We examined somatic mutations of the adenomatous polyposis coli (APC) gene in 63 colorectal tumors (16 adenomas and 47 carcinomas) developed in familial adenomatous polyposis (FAP) and non-FAP patients. In addition to loss of heterozygosity (LOH) at the APC locus in 30 tumors, 43 other somatic mutations were detected. Twenty-one of them were point mutations; 16 nonsense and two missense mutations, and three occurred in introns at the splicing site. Twenty-two tumors had frameshift mutations due to deletion or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
143
0
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 804 publications
(149 citation statements)
references
References 0 publications
3
143
0
3
Order By: Relevance
“…29 This exon also contains the mutation cluster region between codons 1286 and 1513, a region that contains 60%-90% of APC mutations. 6,30 Accordingly, 13/16 (81.3%) of the mutations identified in our study were within these codons.…”
Section: Discussionmentioning
confidence: 58%
“…29 This exon also contains the mutation cluster region between codons 1286 and 1513, a region that contains 60%-90% of APC mutations. 6,30 Accordingly, 13/16 (81.3%) of the mutations identified in our study were within these codons.…”
Section: Discussionmentioning
confidence: 58%
“…Indeed, we previously showed that deletion of cPLA 2 ā£ resulted in fewer and smaller tumors in APC Min mice (19,20). Aneuploidy is a significant feature of sporadic colorectal cancer, and the majority of such cancers carry APC mutations resulting in truncated APC proteins lacking the C terminus (48). It was shown that the C terminus of APC binds microtubules and stimulates polymerization of tubulin in vitro and in vivo (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Biallelic mutation of the APC gene occurs in 45%ā€“80% of colorectal cancers [5ā€“7] and is observed in the earliest detectable lesions [2]. The APC locus was originally identified based on its link to familial adenomatous polyposis coli (FAP), an inherited syndrome of cancer predisposition [8ā€“11].…”
Section: The Apc Genementioning
confidence: 99%
“…Mutations in APC are often frameshifts, insertions or deletions that introduce premature stop codons and lead to the production of a truncated APC protein. Amino acids 1000 to 1600 of APC have been identified as a mutation cluster region that represents roughly 20% of the total (2,843-amino acid) protein yet contains about 60% of all identified mutation sites [7]. The following sections detail functions of the wild-type APC protein, all of which are weakened or lost through the acquisition of pathogenic mutations.…”
Section: Functions Of the Apc Tumor Suppressor Proteinmentioning
confidence: 99%